Konsekuensi Social Media Marketing Activites Kedai Kopi Lokal Kekinian - Muhamad Tegar Harrindi Aji; Sri Vandayuli Riorini (Cakrawala Repositori IMWI, 2023)
This study aims to examine the Antecedents of Consumer Purchase Intentions Contemporary Local Coffee Shop. The dependent variable used in this study is Consumer Purchase Intention. The independent variables used in this study are Interactivity, Informativeness, Personalization, Trendiness, Word of Mouth, Brand Image and Brand Equity. This study collected data using purposive sampling method, data was collected by distributing questionnaires online to 215 respondents. This study uses the Structural Equation Model (SEM) analysis method. The results of this study indicate that: (1) Interactivity has a positive effect on Brand Image, (2) Informativeness has no positive effect on Brand Image, (3) Personalization has a positive effect on Brand Image, (4) Trendiness has a positive effect on Brand Image, (5) Word of Mouth has a positive effect on Brand Image, (6) Brand Image has a positive effect on Brand Equity, (7) Brand Equity has a positive effect on Consumers Purchase Intention.